Analysis of serum cortisol to predict recovery in paediatric sport-related concussion. (21st March 2018) - Ritchie, EV.; Emery, C.; Debert, CT.
ABSTRACT: Objective : To study the relationship between acute serum cortisol following pediatric sport-related concussion (SRC) and clinical outcome measures of symptom burden and length to return to sport (RTS) Methods : Prospective observational study of ice hockey players ages 11–12 recruited prior to the hockey season. Players sustaining a SRC were assessed by a sports medicine physician completed a child Sport Concussion Assessment Tool-3 (childSCAT-3) and serum cortisol samples. Results : Of 636 ice hockey players enrolled, 41 sustained a SRC. In total, 22 serum cortisol samples were collected, with 14 (63.6%) meeting inclusion criteria. Four players presented with abnormally low cortisol and were more likely to experienced more symptoms (17.8 ± 1.9 vs. 7.5 ± 6.0) more severe symptoms (28.5 ± 5.8 vs. 10.2. ±8.8) and took longer RTS (23 ± 13.6 vs. 14.0.7 ± 7.9.). Conclusion : Paediatric ice hockey players following SRC with abnormally low cortisol may be more susceptible to experiencing increase symptom burden and take longer to return to sport than players with population-based normal cortisol.